Strategi Komunikasi Persuasif Pengadilan Agama Dalam Meminimalisir Kasus Perceraian Di Kota Padang - Putri, Mike Mareprillya; Edlina, Ria (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
Communication strategy is a combination of communication planning and communication management to achieve a goal, one of the most basic communication is persuasive communication, namely the procces of influencing the attitudes, opinions and behavior of other people, both verbally and non- verbally. One of the efforts made by the Religious Courts is mediation, in which the judge or non-judge who acts as a mediator is expected to be able to reconcile married couples who are inin the process of divorce. This study aims to determine the persuasive communication strategy of the religious courst is quite good but cannot be said to be optimal because the data on divorce cases fluctuates every year or in inconsistent every year. This means that the persuasive communication strategy of the Padang Religious Courts has not been able to minimize divorce cases. This can be seen from the mediation communication process used, namely : (1) Opening, (2) Information Gathering,(3) Problem Indentification, (4) Solution Search, (5) Negotiation, , (6) Closing